The Efficiency of Islamic Life Insurance in Indonesia: A Two-stages DEA - Tyas, Atika Ayuning (Tamkin Journal, 2023)
The Islamic insurance industry in Indonesia is one of the industries that is experiencing very rapid development every year. This can be seen from the growth of assets and market share that continues to increase, especially in the Islamic life insurance industry. The rapid development of the Islamic life insurance industry has led to a stronger level of competition between companies. To be able to compete in the insurance industry nationally, Islamic life insurance must be able to compete with conventional insurance by improving performance optimally. The purpose of this study is to analyze the efficiency of Islamic life insurance companies and business units in Indonesia for the period 2014-2019 and the factors that influence them. This study used 3 companies and 10 Islamic life insurance business units that issued their financial statements in the 2014-2019 period. The method used in this research is the Data Envelopment Analysis (DEA) method and Tobit. The estimation results show that all companies and business units of Islamic life insurance in Indonesia have not reached the level of performance efficiency and there are still inefficiencies in the use of inputs and outputs. Factors that positively affect efficiency are joint venture dummy, while liquidity ratio and expense to net premium ratio negatively affect the performance efficiency of Islamic life insurance companies and business units in Indonesia.